FAKTOR – FAKTOR YANG MEMPENGARUHI PREDIKSI FINANCIAL DISTRESS PADA PEMERINTAH KABUPATEN/KOTA JAWA TENGAH - Puspitasari, Ervina; Wulandari, Ika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the influence of regional financial ratios including; PAD Effectiveness Ratio, Regional Financial Efficiency Ratio, Income Growth Ratio, Financial Independence Ratio towards predictions of financial distress for Central Java district/city governments. Financial distress is defined as the government's inability to provide public services in accordance with applicable standards and quality. This research uses secondary data, namely the APBD Realization Report in the Audit Results Report on Regional Government Financial Reports (LHP LKPD) for 2019-2021 from the Financial Audit Agency (BPK) Representative of Central Java Province. The method used in this research is binary regression analysis with the help of SPSS version 30 for Windows. The sample selection in this study used a total sampling system, obtaining 105 data from 29 districts and 6 cities. The results of this research show that the PAD Effectiveness Ratio has a negative effect on financial distress, the Regional Financial Efficiency Ratio has no positive effect on financial distress, the Income Growth Ratio has a positive effect on financial distress, the Regional Financial Independence Ratio has no positive effect on financial distress.